Eliciting preferences for waterpipe tobacco smoking using a discrete choice experiment: implications for product regulation - Salloum, Ramzi G; Maziak, Wasim; Hammond, David; Nakkash, Rima; Islam, Farahnaz; Cheng, Xi; Thrasher, James F (BMJ open, 2015)
ObjectivesWaterpipe smoking is highly prevalent among university students, and has been increasing in popularity despite mounting evidence showing it is harmful to health. The aim of this study was to measure preferences for waterpipe smoking and determine which product characteristics are most important to smokers.SettingA large university in the Southeastern USA.ParticipantsAdult waterpipe smokers attending the university (N=367).DesignParticipants completed an Internet-based discrete choice experiment to reveal their preferences for, and trade-offs between, the attributes of hypothetical waterpipe smoking sessions. Participants were presented with waterpipe lounge menus, each with three fruit-flavoured options and one tobacco flavoured option, in addition to an opt out option. Nicotine content and price were provided for each choice. Participants were randomised to either receive menus with a text-only health-warning message or no message.Outcome measuresMultinomial and nested logit models were used to estimate the impact on consumer choice of attributes and between-subject assignment of health warnings respectively.ResultsOn average, participants preferred fruit-flavoured varieties to tobacco flavour. They were averse to options labelled with higher nicotine content. Females and non-smokers of cigarettes were more likely than their counterparts to prefer flavoured and nicotine-free varieties. Participants exposed to a health warning were more likely to opt out.ConclusionsFruit-flavoured tobacco and lower nicotine content labels, two strategies widely used by the industry, increase the demand for waterpipe smoking among young adults. Waterpipe-specific regulation should limit the availability of flavoured waterpipe tobacco and require accurate labelling of constituents. Waterpipe-specific tobacco control regulation, along with research to inform policy, is required to curb this emerging public health threat.